Efficacy of Amblyseius swirskii (Athias-Henriot) (Acari: Phytoseiidae) and Alternaria destruens (Ascomycota: Pleosporaceae) for managing Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) - Mohamed El Aalaoui; Said Rammali; Fatima Zahra Kamal; Alin Ciobică; Bouchaib Bencharki; Abdellatif Rahim; Luminita Diana Hritcu; Laura Romila; Vasile Burlui; Mohamed Sbaghi (Biological Control)
Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) is a major pest of potatoes and other crops, highlighting the need for effective management strategies. This study evaluated the efficacy of a predatory mite and an entomopathogenic fungus, both individually and in combination, against P. solenopsis on potato plants under greenhouse (24.6–35.2 °C) and field conditions (24.9–35.9 °C). The treatments included: untreated control, Tween 80 (TW), the predatory mite Amblyseius swirskii (Athias-Henriot) (Acari: Phytoseiidae) (AS), the fungal pathogen Alternaria destruens (AD), AD + AS, and imidacloprid (ICP) (positive control). Treatment efficacy was evaluated weekly for five weeks, with predators released five days after fungal application. The AD + AS treatment significantly reduced P. solenopsis egg and motile stage counts compared to both initial levels and the individual treatments, reaching 9.88 eggs and 8.11 motile stages in greenhouse trials, and 9.22 eggs and 7.11 motile stages in field trials by week 5. The AD treatment alone caused the highest number of mummified mealybugs by week 5 (28.7 and 26.7 per plant in greenhouse and field trials, respectively), indicating strong pathogen-induced mortality. Amblyseius swirskii populations peaked at 34.8 and 26.7 mites per plant in the greenhouse and field, respectively, by week 3 in the AS alone treatment, with lower densities in the AD + AS treatment due to predator-fungus interactions. The AD + AS treatment effectively reduced P. solenopsis infestations while preserving the visual quality of treated plants (visual quality score > 9.50 by week 5), highlighting its potential for the management of P. solenopsis.